Rolston review of Preston, The Synthetic Age - Rolston, Holmes, 1932-2025, author; Philosophy Documentation Center, publisher (Colorado State University. Libraries, 2018)
Preston has a new worldview, convinced "that humans have utterly transformed the earth" and have a "startling synthetic future." But he should have been more forceful about Anthropocene abuses of power. Further, his discussion of the value of wildness is relegated to a brief, puzzling postscript.
Rolston review of Christopher J. Preston's the Synthetic Age: Outdesigning Evolution, Resurrecting Species, and Reengineering Our World
Rolston review of Preston's the Synthetic Age
Summer 2018.
Rolston reviews Christopher J. Preston's the Synthetic Age: Outdesigning Evolution, Resurrecting Species, and Reengingeering Our World, published by MIT Press, 2018.
Keywords: synthetic age; symbiotic age; wildness; ecosystems; Anthropocene Epoch; future Earth